Odpowiedzi

2010-03-03T17:21:11+01:00
A) -(2x-1)-(3x+1) = - 2x + 1 - 3x - 1 = - 5x

b) (4a-7b)-(2a+3b) = 4a - 7b - 2a - 3b = 2a - 10b

c) (2p-r)+(2r-p) = 2p - r + 2r-p = p + r

d) (x+y)+(x-z)+(z-y) = x + y + x - z + z-y = 2x
1 1 1
2010-03-03T17:21:17+01:00
A; -2x+1-3x-1 b; 4a-7b-2a-3b c; 2p-r+2r-p d; 2x-z
1 4 1
2010-03-03T17:22:03+01:00
A) -2x + 1 - 3x - 1 = -5x ( 1 się redukują)

b) 4a - 7b - 2a - 3b = 2a - 10b

c) 2p - r + 2r - p = p + r

d) x + y + x - z + z - y = 2x ( z i y się redukują)
1 4 1